2017
DOI: 10.1073/pnas.1615504114
|View full text |Cite
|
Sign up to set email alerts
|

Variations in crowding, saccadic precision, and spatial localization reveal the shared topology of spatial vision

Abstract: Visual sensitivity varies across the visual field in several characteristic ways. For example, sensitivity declines sharply in peripheral (vs. foveal) vision and is typically worse in the upper (vs. lower) visual field. These variations can affect processes ranging from acuity and crowding (the deleterious effect of clutter on object recognition) to the precision of saccadic eye movements. Here we examine whether these variations can be attributed to a common source within the visual system. We first compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
162
3
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(202 citation statements)
references
References 90 publications
36
162
3
1
Order By: Relevance
“…This also replicates the vertical meridian asymmetry in both human and non-human primates [5,24]. A more recent study carried out by Greenwood and his colleagues [25] found that crowding zones and saccadic error zones are on average larger along the vertical than horizontal meridian and that there are variations between observers, which is consistent with what we showed in the current study. Our study goes beyond previous ones by showing that the individual differences in acuity, perceived position, and perceived size are unique to the individual observer, are highly reliable, and are not due to a group level effect.…”
Section: Discussionsupporting
confidence: 93%
“…This also replicates the vertical meridian asymmetry in both human and non-human primates [5,24]. A more recent study carried out by Greenwood and his colleagues [25] found that crowding zones and saccadic error zones are on average larger along the vertical than horizontal meridian and that there are variations between observers, which is consistent with what we showed in the current study. Our study goes beyond previous ones by showing that the individual differences in acuity, perceived position, and perceived size are unique to the individual observer, are highly reliable, and are not due to a group level effect.…”
Section: Discussionsupporting
confidence: 93%
“…Figure 3C shows the critical 406 spacing estimates for all observers and the median for the group. Critical spacing estimates 407 19 span an almost-fourfold range, and such between-subjects variability has been reported 408 previously (Greenwood, Szinte, Sayim, & Cavanagh, 2017;Petrov & Meleshkevich, 2011). 409 To control for between-subjects crowding variability in the memory experiment, and 410 therefore control for cortical spacing variability across participants, we adjusted the spatial 411 range of memoranda in the memory experiment to be either 0.75 times ("crowded") or 1.5 412 times ("uncrowded") an observer's critical spacing.…”
supporting
confidence: 52%
“…A link between the oculomotor control and form processing in peripheral vision has been suggested in previous psychophysical studies. By measuring the size of the crowding zone and the saccade-landing zone, Greenwood et al (2017) demonstrated that the saccadic precision and crowding covary across the visual fields. Harrison et al (2013) showed that eye movement preparation effectively reduces the critical spacing of the crowding zone.…”
Section: Orymentioning
confidence: 99%